Low back pain and its relationship with sitting behaviour among sedentary office workers. (November 2019) - Bontrup, Carolin; Taylor, William R.; Fliesser, Michael; Visscher, Rosa; Green, Tamara; Wippert, Pia-Maria; Zemp, Roland
Abstract: The relationships between sedentary lifestyle, sitting behaviour, and low back pain (LBP) remain controversial. In this study, we investigated the relationship between back pain and occupational sitting habits in 64 call-centre employees. A textile pressure mat was used to evaluate and parameterise sitting behaviour over a total of 400 h, while pain questionnaires evaluated acute and chronic LBP. Seventy-five percent of the participants reported some level of either chronic or acute back pain. Individuals with chronic LBP demonstrated a possible trend ( t -test not significant) towards more static sitting behaviour compared to their pain-free counterparts. Furthermore, a greater association was found between sitting behaviour and chronic LBP than for acute pain/disability, which is plausibly due to a greater awareness of pain-free sitting positions in individuals with chronic pain compared to those affected by acute pain. Highlights: Sitting behaviour was analysed in 64 office employees using textile pressure mats. The overall classification accuracy for the different sitting positions was 90%. Subjects with chronic low back pain tended to show a more static sitting behaviour.